Facile High Throughput Wet-Chemical Synthesis Approach Using a Microfluidic-Based Composition and Temperature Controlling Platform - Hu, Yang; Liu, Bin; Wu, Yating; Li, Ming; Liu, Xiaorui; Ding, Jia; Han, Xiaopeng; Deng, Yida; Hu, Wenbin; Zhong, Cheng (Frontiers in Chemistry, 2020)
The wet-chemical technique has been widely applied in material synthesis. In recent years, high throughput (HT) technique has shown its potential in parallel synthesis and the investigation of synthesis parameters. However, traditional ways of HT parallel synthesis require costly equipment and complex operating procedures, restricting their further applications. In this paper, we prepared a cost-effective and timesaving microfluidic-based composition and temperature controlling platform to carry out HT wet-chemical synthesis in a facile and automated workflow. The platform uses a microfluidic chip to generate 20–level concentration gradients of the two reagents and uses 100–channel reactor arrays for wet-chemical synthesis with 5–level temperature gradients. Scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS) were applied to characterize Co–Ni bimetallic powder materials synthesized under 100 different reaction conditions. This platform not only enables one-step determination of the minimum reaction temperature required for a wet-chemical system, but also provides a significant increase of efficiency compared with the traditional wet-chemical approach. The microfluidic-based composition and temperature controlling platform shows promise in facile, efficient, and low-cost HT wet-chemical synthesis of materials.